Conceptual explanation of adolescents' media health literacy: A qualitative content analysis - Samira Daneshvar; Mohtasham Ghaffari; Ali Ramazankhani; Tayebeh Marashi (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: The high use of media among adolescents is involved in negative social and health consequences. Therefore, it is critical that adolescents acquire the skills to interact with media content in a healthy way. This study aimed to identify the dimensions and concept of media health literacy (MHL) among adolescents.MATERIALS AND METHODS: In this qualitative study, specialists (n = 19) in the field of health education and promotion, as well as a wide range of activists in the field of media and communication and adolescents (n = 20), who met the inclusion criteria were participated in this study. Participants were recruited by purposive sampling. Exploratory, open-ended, and face-to-face interviews based on the interview guide were used to elicit participants' perspectives from October 2021 to May 2022 in Tehran, Iran. The interviews were analyzed by content analysis using the inductive method and MAXQDA 2020.RESULTS: A total of eight health education and promotion specialists (20.51%), nine media and communication specialists (23.07%), two software and programming instructors (5.12%), and 20 adolescents (51.28%) were included in the study. Analysis of qualitative data led to the identification of five categories (media literacy (ML), health literacy (HL), media reference, interactive communication literacy, and basic literacy (BL)) and 25 subcategories.CONCLUSIONS: Our findings provide a deep understanding of the concept and domains of MHL. Based on the results, MHL can be defined as a set of knowledge and individual skills needed in the fields of ML, HL, interactive communication literacy, media reference, and BL, which help achieve the appropriate state of MHL among adolescents and its improvement. It is hoped that these findings are used to guide the development of interventions for MHL.